The Effect of Digital Noise Reduction on Annoyance and Speech Perception in Low and High Acceptable Noise Level Groups - Shetty, Hemanth Narayan; Nanjundaswamy, Navya Bilijagalemole (International Archives of Otorhinolaryngology, 2019)
Introduction Studies have reported that although speech perception in noise was unaltered with and without digital noise reduction (DNR), the annoyance toward noise measured by acceptable noise level (ANL) was significantly improved by DNR with the range between 2.5 and 4.5 dB. It is unclear whether a similar improvement would be observed in those individuals who have an ANL ≥ 14 dB (predictive of poor hearing aid user) often rejects their aid because of annoyance toward noise.Objectives (a) To determine the effect of activation of DNR on the improvement in the aided ANL from low- and high-ANL groups; and (b) to predict the change in ANL when DNR was activated.Method Ten bilateral mild to severe sloping sensorineural hearing loss (SNHL) participants in each of the low- and high-ANL groups were involved. These participants were bilaterally fitted with receiver in canal (RIC) hearing aids (Oticon, Smorum, Egedal, Denmark) with a DNR processor. Both SNR-50% (Signal to noise ratio (in dB) required to achieve 50 % speech recognition) and ANL were assessed in DNR-on and DNR-off listening conditions.Results Digital noise reduction has no effect on SNR-50 in each group. The annoyance level was significantly reduced in the DNR-on than DNR-off condition in the low-ANL group. In the high-ANL group, a strong negative correlation was observed between the ANL in DNR off and a change in ANL after DNR was employed in the hearing aid (benefit). The benefit of DNR on annoyance can be effectively predicted by baseline-aided ANL by linear regression.Conclusion Digital noise reduction reduced the annoyance level in the high-ANL group, and the amount of improvement was related to the baseline-aided ANL value.
Keywords: noise reduction; hearing aid; annoyance; speech perception